4, 6-Substituted-1H-Indazoles as potent IDO1/TDO dual inhibitors. Issue 6 (15th March 2019) - Yang, Lingling; Chen, Yang; He, Junlin; Njoya, Emmanuel Mfotie; Chen, Jianjun; Liu, Siyan; Xie, Congqiang; Huang, Wenze; Wang, Fei; Wang, Zhouyu; Li, Yuzhi; Qian, Shan
Graphical abstract: Highlights: 38 Indazole derivatives were synthesized. Compound35 displayed the most IDO1 inhibitory potency. Compound35 was identified as an IDO1/TDO dual inhibitor. Compound35 decreased the INFγ-induced IDO1 expression. Compound35 exhibited in vivo antitumor activity in CT26 model. Abstract: Indoleamine 2, 3-dioxygenase 1 (IDO1) and tryptophan 2, 3-dioxygenase (TDO) are constitutively overexpressed in many types of cancer cells and exert important immunosuppressive functions. In this article, a series of 4, 6-substituted-1 H -indazole derivatives were synthesized and evaluated the inhibitory activities against IDO1 and TDO, as well as their structure-activity relationships (SARs). Among these, compound35 displayed the most IDO1 inhibitory potency with an IC50 value of 0.74 μM in an enzymatic assay and 1.37 μM in HeLa cells. Quantitative analysis of the Western blot results indicated that35 significantly decreased the INFγ-induced IDO1 expression in a concentration-dependent manner. In addition, 35 showed promising TDO inhibition with an IC50 value of 2.93 μM in the enzymatic assay and 7.54 μM in A172 cells. Moreover, compound35 exhibited in vivo antitumor activity in the CT26 xenograft model. These findings suggest that 1 H -indazole derivative35 is a potent IDO1/TDO dual inhibitor, and has the potential to be developed for IDO1/TDO-related cancer treatment.